PENERAPAN PROJECT STEM DALAM PEMBELAJARAN IPA SECARA DARING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF PADA ASPEK FLEXIBILITY SISWA SMP PADA MATERI PESAWAT SEDERHANA - Haidi, Rahmat Zul; Zulirfan, Zulirfan; M. Rahmad, M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The era of the industrial revolution 4.0 requires quality human resources with 21st century skills that must be possessed such as critical thinking, creativity, collaboration and communication. The purpose of this research was to get an idea of the extent to which the initial conditions before and after learning regarding the level of creative thinking skills in the aspect of flexibility. The type of research used is a quasi-experimental design using a non-equivalent pretest posttest control group design. The population of this research were students of class VIII SMPN 21 Pekanbaru as many as 120 students who were distributed in three classes. The samples of this research were students of class VIII 8 as the control class with a total of 28 students and class VIII 9 students as the experimental class with a total of 32 students. The sample was determined based on the results of the normality test and homogeneity test. The data collection instrument was a test of creative thinking skills on the flexibility aspect of class VIII junior high school students for the context of simple airplane material. Data analysis was carried out by descriptive analysis assisted by the SPSS version 20 application. The results showed that there were differences in the level of creative thinking skills in the flexibility aspect between the control group and the experimental group and the application of the learning model using the STEM project approach was effectively used to improve the creative thinking skills of junior high school students in aspects of flexibility in learning Natural Sciences Physics online.Keywords: STEM Project Science Learning, Creative Thinking Skills, Flexibility Aspect, Simple Plane